1988
DOI: 10.1530/jrf.0.0820353
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of non-steroidal anti-inflammatory drugs in male rabbits after acute and chronic administration and effect of chronic treatment on seminal prostaglandins, sperm quality and fertility

Abstract: Summary. The pharmacokinetics of various non-steroidal anti-inflammatory drugs were determined to find dosage regimens by which drug concentrations known as active from human anti-inflammatory therapy could be reached and maintained in rabbits during continued administration. Based on the pharmacokinetics and si de\ x=req-\ effects of the different drugs, phenylbutazone was selected for the fertility experiments. Treatment of male rabbits with phenylbutazone for 9 consecutive days significantly reduced seminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…[8687] Treatment with low-dose NSAIDs was shown to improve sperm quality and fertility in an animal model. [88] Interestingly, carnitine administration was reported to promote the accumulation of prostaglandin E2 in seminal fluid. [89] Therefore, the concomitant administration of NSAIDs with carnitines may have a complementary mechanism that facilitates the positive effects of carnitine therapy while counteracting excess prostaglandin production.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8687] Treatment with low-dose NSAIDs was shown to improve sperm quality and fertility in an animal model. [88] Interestingly, carnitine administration was reported to promote the accumulation of prostaglandin E2 in seminal fluid. [89] Therefore, the concomitant administration of NSAIDs with carnitines may have a complementary mechanism that facilitates the positive effects of carnitine therapy while counteracting excess prostaglandin production.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…However, a certain level of prostaglandins and oxidative stress is required for physiologic sperm functioning. Although long-term treatment with NSAIDs at low doses has been associated with improved sperm quality and fertility,[88] in vitro experiments have illustrated that higher dosage of NSAIDs may inhibit sperm motility. [90] NSAIDs administered via a suppository are thought to exert a more pronounced and direct effect on seminal plasma due to rectal-prostatic lymphatic pathways.…”
Section: Non-steroidal Anti-inflammatory Drugsmentioning
confidence: 99%
“…Hydrophilic NSAIDs were less active than C, whose lipophilia facilitate absorption [176]. An animal model showed that chronic treatment with NSAIDs at low doses improved sperm quality and fertility [178]. Carnitine administration was found to increase E2 prostaglandin concentration [179], which affects sperm count [180,181].…”
Section: Therapymentioning
confidence: 99%
“…ROS concentration is critical in regulating sperm function; if too high it inhibits sperm motility and modifies the morphology to the point of producing McLeod stress patterns [10], but too low and it down-regulates capacitation and acrosomal reactions [23]. Confirming this kind of 'spot therapy', experimental models showed that chronic treatment with NSAIDs at low doses improved sperm quality and fertility [24], and in vitro experiments showed that a high cinnoxicam concentration in seminal plasma inhibited sperm motility [25].…”
Section: Discussionmentioning
confidence: 99%